Characterization of the motor performance in infants with a diagnosis of cerebral palsy in process of rehabilitation: The importance of the proactivity of caregivers - Herrero, Dafne; Monteiro, Carlos Bandeira de Mello; Massetti, Thais; da Silva, Talita Dias; de Barros, Aline Rita; Valenti, Vitor E. [UNESP]; de Abreu, Luiz Carlos (My University, 2012)
Introduction: The progress in technology, associated to the high survival rate in premature newborn infants in neonatal intensive care units, causes an increase in morbidity. Individuals with CP present complex motor alterations, with primary deficits of abnormal muscle tone affecting posture and voluntary movement, alteration of balance and coordination, decrease of force, and loss of selective motor control with secondary problems of contractures and bone deformities. Objective: The aim of this work is to describe the spontaneous movement and strategies that lead infants with cerebral palsy to move. Methods: Seven infants used to receive assistance at the Essential Stimulation Center of CIAM (Israeli Center for Multidisciplinary Support - Philanthropic Institution), with ages ranging between six and 18 months with diagnosis of Cerebral Palsy (CP) were assessed. Results: The results show the difficulty presented by the infants with respect to the spontaneous motor functions and the necessity of help from the caregiver in order to perform the functional activity (mobility). Prematurity prevails as the major risk factor among the complications. Conclusion: The child development can be understood as a product of the dynamic interactions involving the infant, the family, and the context. Thus, the social interactions and family environment in which the infant live may encourage or limit both the acquisition of skills and the functional independence.
Keywords: Cerebral palsy; Infant; Movement; Musculoskeletal development